Summary of taxonomy changes ratified by the International Committee on Taxonomy of Viruses (ICTV) from the Fungal and Protist Viruses Subcommittee, 2025 - Sabanadzovic, Sead; Abergel, Chantal; Ayllón, Marı́a A.; Botella, Leticia; Canuti, Marta; Chiba, Yuto; Claverie, Jean-Michel; Coutts, Robert H.A.; Daghino, Stefania; Donaire, Livia; Forgia, Marco; Hejna, Ondřej; et al. (Society for General Microbiology, 2025)
An erratum of this article has been published full details can be found at 10.1099/jgv.0.002144 The Fungal and Protist Viruses Subcommittee (SC) of the International Committee on Taxonomy of Viruses (ICTV) has received a total of eight taxonomic proposals for the 2024 annual cycle. The extent of proposed changes varied, including nomenclatural updates, creation of new taxa and reorganization of established taxa. Following the ICTV procedures, all proposals were reviewed and voted upon by the members of the Executive Committee with ratification in March 2025. As a result, a total of 52 species in the families Botourmiaviridae and Marnaviridae were renamed to comply with the mandated binomial format. A new genus has been added to the dsRNA virus family Amalgaviridae, while two new families, Splipalmiviridae (Wolframvirales) and Mycoalphaviridae (Hepelivirales), were created to classify new groups of positive-sense (+) RNA mycoviruses. The class Arfiviricetes (Cressdnaviricota) was expanded by a new order Lineavirales and a new family Oomyviridae of ssDNA viruses. Additionally, a ne class Orpoviricetes was created in the kingdom Orthornavirae to classify a group of bisegmented (+)RNA viruses reported from fungi and oomycetes. Finally, the order Pimascovirales was reorganized to better depict evolutionary relationships of pithoviruses and related viruses with large dsDNA genomes. The summary of updates in the taxonomy of fungal and protist viruses presented here is limited to taxa within the remit of this Subcommittee. For information on taxonomy changes on other fungal viruses closely related to animal and/or plant viruses, please see reports from sister ICTV Subcommittees (i.e. Plant Virus SC and Animal dsRNA and ssRNA(−) Viruses SC).
Keywords: viruses; taxonomy